Tropical home gardens: Biodiverse, climate-resilient and nutrition-sensitive forms of agriculture: A compilation of abstracts - Reyes-Sacdalan, N.B.; Gonsalves, Julian; Hunter, Danny; Monville-Oro, Emilita; Anunciado, M.S.S. (2025)
This compilation features 67 abstracts of publications on tropical home gardens, primarily in Asia. It highlights key findings and recommendations on traditional home gardening practices and programs, providing guidance for designing effective interventions. Additionally, it offers insights for policymakers on leveraging home gardens as a strategy to enhance nutrition, education, agriculture, and land use planning.